ANALISIS KARAKTERISTIK FILTRASI DENGAN MEDIA BIOCHAR UNTUK PENURUNAN KONSENTRASI AMMONIUM DAN FOSFAT - Filemon Bram Gunas Junior; Shinta Enggar Maharani; I Made Wahyu Wijaya (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2026)
This study is motivated by the high concentration of nutrients, particularly ammonium (NH₄⁺) and phosphate (PO₄³⁻), in domestic wastewater, which can lead to eutrophication if not properly treated. The objective of this research is to analyze the hydraulic characteristics and filtration performance of biochar media in a two-compartment filtration system for domestic wastewater treatment. The study was conducted experimentally using a laboratory-scale filtration unit with effective dimensions of 200 mm × 200 mm and a media height of 700 mm. The system was operated under continuous flow conditions at a discharge rate of 50 L/h for 3 hours per day. The analyzed parameters included filtration effectiveness duration, bed volume (BV), head loss, permeability coefficient (K), and hydraulic retention time (HRT), as well as the removal efficiency of ammonium and phosphate, measured using spectrophotometric methods. The results showed that the filtration effectiveness duration reached 28.17 hours, with a total treated water volume of 1.4083 m³, equivalent to 66.45 BV. The head loss value of 0.50 m remained relatively stable throughout the operation, indicating no significant clogging of the media. The permeability coefficient of 3.12 × 10⁻⁴ m/s indicates moderate to high permeability, with an HRT ranging from 21 to 25 minutes. The biochar media achieved ammonium removal efficiencies of 65–75% and significantly reduced phosphate concentrations, with the highest efficiency observed at the initial stage before declining due to media saturation.